2012
DOI: 10.2105/ajph.2011.300641
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Impact of Social Discrimination and Financial Hardship on the Sexual Risk of HIV Among Latino and Black Men Who Have Sex With Men

Abstract: Future prevention research and program designs should specifically address the differential impact of social discrimination and financial hardship on lack of social support and risky sexual situations among Latino and Black MSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
124
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(136 citation statements)
references
References 40 publications
8
124
3
Order By: Relevance
“…These results were expected and are consistent with a recent large study of Black and Latino MSM in which researchers found that financial hardship was associated with condomless anal intercourse with sero-discordant or sero-unknown partners. 41 Several hardships were associated with HIV risk but in the direction that was not anticipated. Incarceration history was associated with decreased likelihood of CRAI, and recent conviction was associated with decreased likelihood of having ≥2 male sex partners.…”
Section: Discussionmentioning
confidence: 96%
“…These results were expected and are consistent with a recent large study of Black and Latino MSM in which researchers found that financial hardship was associated with condomless anal intercourse with sero-discordant or sero-unknown partners. 41 Several hardships were associated with HIV risk but in the direction that was not anticipated. Incarceration history was associated with decreased likelihood of CRAI, and recent conviction was associated with decreased likelihood of having ≥2 male sex partners.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, participants were asked if they had ever disclosed their same sex behavior to anyone else (labeled as being "out"). Lack of social support was measured using a 5-item scale developed for the Brothers y Hermanos study (Ayala, Bingham, Kim, Wheeler, & Millett, 2012;J. L. Lauby et al, 2012)).…”
Section: Methodsmentioning
confidence: 99%
“…Youth sexual behavior is influenced by a host of sociocontextual factors, including characteristics of families, community norms, early childhood environments, and traumatic experiences. [3][4][5] However, existing studies of HIV risk among YBMSM tend to focus on more proximate influences on sexual behavior (e.g., substance abuse, partner characteristics), with comparatively less emphasis on developmental and contextual influences over the life-course.…”
Section: Introductionmentioning
confidence: 99%